Fabricating PCPDTBT/PC61BM organic solar cells using the PVD method - Or Gindi; Zeev Fradkin; Anat Itzhak; Sofiya Kolusheva; Peter Beker (Heliyon)
A study conducted to investigate the fabrication of organic solar cells based on PC61BM:PCPDTBT using the Physical Vapor Deposition (PVD) method. The research carries out a number of analyses for structural evaluations (XRD and ESEM), compositional change (XPS and FTIR), and functional assessment (absorption and I-V testing), with the goal of understanding the materials’ properties, their behavior during deposition and the resulting characteristics of the fabricated solar cells. While demonstrating promise, the PVD method faces challenges in the maintenance of electrical attributes during vaporization, and the need for further optimization. The findings highlight both the advantages and limitations of the method and point the way toward achieving optimal outcomes in the manufacture of organic solar cells using PVD. The main scientific contribution of this manuscript lies in the application of the PVD method for fabricating PCPDTBT. The final device features a working solar cell device made of the materials discussed above with Cell size of 0.0026mm2, cell efficiency of about 0.18% and thickness of 309 nm–400nm. These results showcasing the possibility of building and fabricating organic cells with the PVD method.